Find the value of : ∫ 0 2 π tan x ln ( sin x ) d x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Really Intelligent. Good Solution.
Really good solution, Brilliant problem.
Brilliant solution! But is there a way to solve this without the taylor series?
Log in to reply
Challenge's accepted bro. Take a look my edited solution. ⌣ ¨
Relevant wiki: Polylogarithm
I = ∫ 0 2 π tan x ln ( sin x ) d x = ∫ 0 2 π cos x sin x ln ( sin x ) d x = ∫ 0 1 1 − u 2 u ln u d u = 2 1 ∫ 0 1 ( 1 − u ln u − 1 + u ln u ) d u = 2 1 ∫ 0 1 u ln ( 1 − u ) d u − 2 1 ( ln ( 1 + u ) ln x ∣ ∣ ∣ ∣ 0 1 − ∫ 0 1 u ln ( 1 + u ) d u ) = − 2 Li 2 ( 1 ) − 2 1 ( 0 − ∫ 0 − 1 t ln ( 1 − t ) d t ) = − 2 Li 2 ( 1 ) − 2 Li 2 ( − 1 ) = − 1 2 π 2 + 2 4 π 2 = − 2 4 π 2 ≈ − 0 . 4 1 1 Let u = sin x ⟹ d u = cos x d x By ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x By integration by parts Li 2 ( z ) is dilogarithm function. Let t = − u
Problem Loading...
Note Loading...
Set Loading...
Rewrite ∫ 0 2 π tan x ln ( sin x ) d x = ∫ 0 2 π cos x sin x ln ( sin x ) d x . Let y = cos x , then d y = − sin x d x . For 0 < x < 2 π , we have 0 < y < 1 . Now, it turns out to be ∫ 0 2 π cos x sin x ln ( sin x ) d x = ∫ 0 2 π cos x sin x ln ( 1 − cos 2 x ) d x = − 2 1 ∫ 0 1 y ln ( 1 − y 2 ) d y . ( 1 ) Next, use Maclaurin series for natural logarithm : ln ( 1 − y 2 ) = − n = 1 ∑ ∞ n y 2 n . ( 2 ) Substituting ( 2 ) to ( 1 ) yields 2 1 ∫ 0 1 y ln ( 1 − y 2 ) d y = − 2 1 ∫ 0 1 n = 1 ∑ ∞ n y y 2 n d y = − 2 1 n = 1 ∑ ∞ ∫ 0 1 n y 2 n − 1 d y = − 4 1 n = 1 ∑ ∞ n 2 y 2 n ∣ ∣ ∣ ∣ y = 0 1 = − 4 1 n = 1 ∑ ∞ n 2 1 . The infinite series above is defined as Riemann zeta function ζ ( 2 ) = 6 π 2 . Thus, ∫ 0 2 π tan x ln ( sin x ) d x = − 4 1 n = 1 ∑ ∞ n 2 1 = − 4 1 ⋅ 6 π 2 = − 2 4 π 2 ≈ − 0 . 4 1 1 2 3 4
Here is another way to solve the integral without using Taylor series. Substituting y = x 2 , we obtain ∫ 0 1 x ln ( 1 − x 2 ) d x = 2 1 ∫ 0 1 y ln ( 1 − y ) d y Using the fact that y ln ( 1 − y ) = − ∫ 0 1 1 − x y 1 d x then 2 1 ∫ 0 1 y ln ( 1 − y ) d y = − 2 1 ∫ y = 0 1 ∫ x = 0 1 1 − x y 1 d x d y . Using transformation variable by setting ( u , v ) = ( 2 x + y , 2 x − y ) so that ( x , y ) = ( u − v , u + v ) and its Jacobian is 2 . Therefore − 2 1 ∫ y = 0 1 ∫ x = 0 1 1 − x y 1 d x d y = − ∬ A 1 − u 2 + v 2 d u d v , where A is the square with vertices ( 0 , 0 ) , ( 2 1 , − 2 1 ) , ( 1 , 0 ) , and ( 2 1 , 2 1 ) . Exploiting the symmetry of the square, we obtain ∬ A 1 − u 2 + v 2 d u d v = 2 ∫ u = 0 2 1 ∫ v = 0 u 1 − u 2 + v 2 d v d u + 2 ∫ u = 2 1 1 ∫ v = 0 1 − u 1 − u 2 + v 2 d v d u = 2 ∫ u = 0 2 1 1 − u 2 1 arctan ( 1 − u 2 u ) d u + 2 ∫ u = 2 1 1 1 − u 2 1 arctan ( 1 − u 2 1 − u ) d u . Since arctan ( 1 − u 2 u ) = arcsin u , and if θ = arctan ( 1 − u 2 1 − u ) then tan 2 θ = 1 + u 1 − u and sec 2 θ = 1 + u 2 . It follows that u = 2 cos 2 θ − 1 = cos 2 θ and θ = 2 1 arccos u = 4 π − 2 1 arcsin u . Thus ∬ A 1 − u 2 + v 2 d u d v = 2 ∫ u = 0 2 1 1 − u 2 arcsin u d u + 2 ∫ u = 2 1 1 1 − u 2 1 ( 4 π − 2 1 arcsin u ) d u = [ ( arcsin u ) 2 ] u = 0 2 1 + [ 2 π arcsin u − 2 1 ( arcsin u ) 2 ] u = 2 1 1 = 3 6 π 2 + 4 π 2 − 8 π 2 − 1 2 π 2 + 7 2 π 2 = 1 2 π 2 and the result follows.
# Q . E . D . #